Edukasi Perencanaan Keuangan Bagi Calon Pemagang ke Jepang - Eko Ahmad; Widi Hastomo (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2020)
This community service aims to provide planning training to Japanese champions so that later they can manage their finances in accordance with their individual financial goals. Educational participants are prospective Japanese apprentices. Totaling participants are 40 participants who are divided into 2 classes. The method in this activity is in the form of education as well as training. Educational methods include providing material that is about financial literacy, financial planning, financial goals, and business introduction. The Training Method includes participants directly doing the practice by filling out the worksheets provided in accordance with the material provided. Financial literacy test results increased by 35%, financial planning increased by 35%, financial goals increased by 25%, business introduction increased by 25%. For the evaluation of activities 85% of respondents (participants and LPK Bangkit staffs) responded positively to this activity the rest needs to be corrected regarding the large amount of material and the short time. Overall, this activity ran smoothly and provided positive benefits for the participants and Bangkit LPK.